Whole genome sequence of seaweed endophyte Bacillus halotolerans strain AUPP for antagonistic activity against Fusarium incarnatum causing chilli fruit rot - Hudson Ann Suji; Karuppiah Manikandan; Appusami Sudha; Arjunan Muthukumar; Chelladurai Jeyalakshmi; Muniyandi Charumathi; Manickam Rajesh; Thankaraj Suthin Raj (Scientific Reports)
Abstract Endophytes isolated from seaweeds emerge as promising biocontrol agents against broad spectrum of plant diseases. The endophytic bacteria were isolated from the seaweed (Sargassum wightii) to manage the chilli fruit rot pathogen Fusarium incarnatum. The antifungal activity of the isolated bacteria was tested by dual culture assay and plant growth-promoting activity was also tested by the standard paper towel method. The biocontrol strain AUPP displayed strong antifungal against Fusarium incarnatum (80.23%) and plant growth-promoting activity including seed germination (97.60%) and vigour index (1287.34) under in-vitro conditions. The identity of the endophytic bacteria was established through whole genome sequence analysis which showed promising biocontrol and plant growth-promoting activity. Whole genome sequence analysis of the biocontrol Bacillus halotolerans strain AUPP revealed the genomic information including 4,166,288 bp genome size, 18 contigs and 43.6% GC content. Genome analysis revealed the 15 secondary metabolite regions associated with the production of secondary metabolites and genes responsible for the antifungal activity. Furthermore, we identified multiple antibiotics, multidrug-resistant genes and a CRISPR sequence. This study presents the first whole genome sequence of B. halotolerans isolated from seaweed in India. These findings highlight its potential for broad-spectrum plant disease control.